-24=-4(a+9)

Simple and best practice solution for -24=-4(a+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24=-4(a+9) equation:



-24=-4(a+9)
We move all terms to the left:
-24-(-4(a+9))=0
We calculate terms in parentheses: -(-4(a+9)), so:
-4(a+9)
We multiply parentheses
-4a-36
Back to the equation:
-(-4a-36)
We get rid of parentheses
4a+36-24=0
We add all the numbers together, and all the variables
4a+12=0
We move all terms containing a to the left, all other terms to the right
4a=-12
a=-12/4
a=-3

See similar equations:

| 100=-5q-5q-10 | | 12y-10=14y | | 3(2+u)-u=6+u(u+1) | | 6=2a-2 | | x+4+2x-6=90 | | 100=-5q–5q–10 | | 6(v+5)=-2(5v-8)+6v | | 7x+11-5x-25=-6 | | 7x+12=2x-3 | | 2(6+y)-5y=21 | | 7(x-3)=15+5 | | d22=60 | | 2(6+y)–5y=21 | | (2x+15)+61=180 | | 4y+2=6y-20 | | 9w-8+2(2w+2)=-2(w+7) | | 2x+1=3x+13 | | 4.50.25a+0.5=4.5 | | 2x+1=3×+13 | | -21=s-17 | | -2r=-r+11 | | 6(y+3)+3=9 | | 10(x−1)=5(x+2) | | 8h-12=6h | | 3x+9=8x+14 | | t-10/4=-4 | | 17+w=19 | | t–104=-4 | | -5a+10a=10 | | -4=2(s+5) | | 1=-6z+5z | | 5(x+3)–3x=55 |

Equations solver categories